Pengaruh Profitabilitas Dan Struktur Modal Terhadap Nilai Perusahaan Pada Pt. Astra Internasional Tbk. - Galih Purnama Siddik; Asyfiah Asri; Tarmin (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
Data in this study comes from the year-end financial statements of PT. Astra Internasional Tbk for 6 years period 2017-2022. This study used quantitative methods.The independent variables of this study are profitability calculated using Return On Equity (ROE) and Capital Structure calculated using Debt to Equity Ratio (DER). Company value is calculated using Price Book Value (PBV) to be the dependent variable. Based on the results of the t test, the effect of Profitability (ROE) on Company Value (PBV) obtained a calculated t value < t table (-0.425 < 2.132), then H10 is accepted and H1a is rejected meaning that Profitability (ROE) has no effect on Company Value (PBV). The results of the t test of the effect of Capital Structure (DER) on Company Value (PBV) obtained the value of t calculated > t table (3.193 > 2.132), then H20 is rejected and H2a is accepted meaning that Capital Structure (DER) affects Company Value ( PBV). Based on the results of the F test of the effect of Profitability (ROE) and Capital Structure (DER) on Company Value (PBV), the F value is calculated > F table (5.667 > 5.46), then Ha is accepted and Ho is rejected meaning that Profitability (ROE) and Capital Structure (DER) simultaneously affect Company Value (PBV).